2012
DOI: 10.1007/s00431-012-1673-0
|View full text |Cite
|
Sign up to set email alerts
|

RSV hospitalisation and healthcare utilisation in moderately prematurely born infants

Abstract: Respiratory syncytial virus (RSV) infection is associated with chronic respiratory morbidity in infants born very prematurely. Our aims were to determine if infants born moderately prematurely (32--35 weeks of gestation) who had had an RSV hospitalisation, compared to those who had not, had greater healthcare utilisation and related cost of care in the first 2 years. Two thousand and sixty-six eligible infants' records were examined to identify three groups: 20 infants admitted for an RSV lower respiratory tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 23 publications
2
36
0
Order By: Relevance
“…Other studies confirmed that RSV-infected children pay a significantly greater number of visits to the doctor than their uninfected counterparts [20],[34]. RSV-infected preterm children 32-35 weeks GA have an average of 12.4 doctor visits during their first two years of life (median?=?12; range?=?1-27) for any cause and 5 visits on average (median?=?4; range?=?0-14) for respiratory causes, whereas the same data for children with no respiratory pathology were 9.4 (median?=?8; range?=?0-34) and 2.9 (median?=?2; range?=?0-17), respectively [34]. A multicenter Spanish study reported that 18.8% of first AB episodes in children under the age of 2 were diagnosed in primary care [30].…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Other studies confirmed that RSV-infected children pay a significantly greater number of visits to the doctor than their uninfected counterparts [20],[34]. RSV-infected preterm children 32-35 weeks GA have an average of 12.4 doctor visits during their first two years of life (median?=?12; range?=?1-27) for any cause and 5 visits on average (median?=?4; range?=?0-14) for respiratory causes, whereas the same data for children with no respiratory pathology were 9.4 (median?=?8; range?=?0-34) and 2.9 (median?=?2; range?=?0-17), respectively [34]. A multicenter Spanish study reported that 18.8% of first AB episodes in children under the age of 2 were diagnosed in primary care [30].…”
Section: Resultsmentioning
confidence: 90%
“…RSV involvement has been confirmed in 0.7% to 8% of COPD flare-ups [34]-[40]. RSV presence has also been detected in 11% of patients admitted with pneumonia, COPD (11%), heart failure (5%), and asthma (7%) [22].…”
Section: Resultsmentioning
confidence: 99%
“…F protein | human respiratory syncytial virus | neutralizing antibodies R espiratory syncytial virus (RSV) is a highly contagious human pathogen, infecting the majority of infants before age 2 y, and is the leading cause of viral bronchiolitis and viral pneumonia in infants and children (1,2). RSV remains a top priority for vaccine development, as thousands of deaths are recorded worldwide each year because of complications from infection (3).…”
mentioning
confidence: 99%
“…In another study, the 2-year-long health expenditures of 20 cases admitted due to RSV + RTI of out the premature infants born 32-35 weeks were compared with 30 infants admitted due to RSV -RTI and similarly with 108 infants without RTI, it was reported that the health expenditures in the RSV + group were significantly higher than the other two groups (16). In our study, it was found that the average direct medical hospitalization cost of a patient with RSV + LRTI was $910 and that of a RSV -patients $1028 (p>0.05) and in contrast to the studies mentioned above, RSV + LRTI costs were not higher than RSV -LRTI (Table 2).…”
Section: Discussionmentioning
confidence: 99%